Evidence that the Platelet Integrin αIIbβ3 Is Regulated by the Integrin-Linked Kinase, ILK, in a PI3-Kinase Dependent Pathway - Pasquet, Jean-Max; Noury, Malia; Nurden, Alan T. (Thrombosis and Haemostasis, 2002)
Platelet aggregation is mediated by the integrin αIIbβ3 which is activated by intracellular signals during platelet activation. We have attempted to determine if ILK (“Integrin-Linked Kinase”) is involved in the regulation of αIIbβ3 function. ILK co-immunoprecipitated with β3 in stimulated platelets. Using confocal microscopy, ILK was detected in the cytoplasm of resting platelets. ADP or PMA stimulation led to its translocation to the plasma membrane. In parallel, there was a transient increase in ILK kinase activity, association with and phosphorylation of β3. Inhibition of PI3-kinase by two unrelated inhibitors (wortmannin and LY294002) prevented ILK-related functions. However, it did not prevent the conformational change in αIIbβ3 (shown by PAC-1 binding), although integrin affinity for fibrinogen was decreased as measured using FITC-fibrinogen. Furthermore, aggregate formation was reduced. Thus ILK transiently associates with and phosphorylates β3 in a PI3-kinase dependent manner suggesting that it participates at an intermediate stage in a critical mechanism for assuring large stable aggregates.
Keywords: Integrin αIIbbβ3; platelets; integrin linked kinase; activation mechanisms